The Effectiveness of E-Book Learning Media on Business Communication Material for Students of SMK PGRI 1 Jombang (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study aims to explore the effectiveness of e-book learning media in improving students' learning outcomes in Business Communication subjects at SMK PGRI 1 Jombang. The research utilized a quasi-experimental design with a nonequivalent control group. A total of 73 students participated, divided into two groups: the experimental group using e-books as a learning medium and the control group receiving traditional teaching methods. Data were collected through standardized multiple-choice tests, and independent sample t-tests were employed for data analysis. The results showed a significant difference in the learning outcomes between the two groups, with the experimental group achieving an average score of 88.03, compared to the control group's average of 73.89, with a p-value of less than 0.001. These findings indicate that e-book learning media has a positive impact on student engagement, motivation, and conceptual understanding in vocational education settings. The use of e-books as an interactive learning tool appears to enhance students' ability to grasp complex business communication concepts, providing them with a more engaging and dynamic learning experience. This study contributes to the development of digital-based pedagogies and offers empirical evidence supporting the integration of e-books and similar e-learning tools into vocational school curricula. Based on the findings, it is recommended that educational institutions, particularly vocational schools, consider adopting e-book media as a part of their teaching strategies to improve students' learning outcomes, as well as to foster greater digital literacy. The study highlights the importance of integrating modern technology into education to better align with the evolving digital landscape in teaching and learning practices.